STRATEGI KOMUNIKASI KOMISI PEMILIHAN UMUM (KPU) PROVINSI MALUKU DALAM MENINGKATKAN PARTISIPASI MASYARAKAT DALAM PEMILUKADA TAHUN 2018 - ZACHARIAS TEHUBIJULUW (BADATI, 2020)
This study aims to determine and understand the communication strategy of the Maluku Provincial KPU in increasing community participation in the 2018 elections. The research approach uses descriptive qualitative. Data was collected through interviews using interview guidance instruments. The results showed that the Maluku Provincial KPU communication strategy in increasing public participation in the 2018 elections included communication planning, mapping of voter segmentation according to typology and voter characteristics, audience analysis and segmentation, media selection and program evaluation